Effects of axial dispersion on fixed bed design for binary ion-exchange under liquid phase control - Núñez, María; Arrieta, Idelfonso; Sarmiento, Carmen; López, Arelis; García, Cézar (Rev. Téc. Fac. Ing. Univ. Zulia)
Véase archivo PDF